Reductions in claudin-1 may enhance susceptibility to herpes simplex virus 1 infections in atopic dermatitis - De Benedetto, Anna; Slifka, Mark K.; Rafaels, Nicholas M.; Kuo, I-Hsin; Georas, Steve N.; Boguniewicz, Mark; Hata, Tissa; Schneider, Lynda C.; Hanifin, Jon M.; Gallo, Richard L.; Johnson, David C.; Barnes, Kathleen C.; et al. (Journal of allergy and clinical immunology, 2011)
To the Editor: Atopic dermatitis (AD) is the most common inflammatory skin disease, affecting up to 20% of children in the United States, and is characterized by an increased susceptibility to cutaneous infections.1,2 One in 10 subjects with AD has difficulty clearing cutaneous infections with a host of viruses including herpes simplex, vaccinia, human papilloma, and/or molluscum contagiosum.1 This typically manifests as more extensive cutaneous and sometimes systemic disease and/or resistance to standard therapies.